A união mística na Enéada VI, 9, de Plotino - Almeida, Rodrigo Moreira de (2017)
This work investigates the concept of "mystical union" with the One in the Ennead VI, 9 of Plotinus, entitled On the Good or the One. Initially, it examines this concept in the larger context of Plotinus' metaphysics, in which it plays a fundamental role, as the ultimate goal of philosophical life. This first part of the inquiry also proposes a diachronic reading of Plotinus" philosophy, with the aim of understanding the position of Neoplatonism within the history of Ancient Philosophy and Plotinus' appropriation of the previous philosophical tradition. Next, it proceeds to study the characteristics of the mystical union with the One, as well as the preliminary stages of realization of this union and the sense in which must be understood the adjective "mystic", which qualifies it. The dissertation concludes with a study on the importance of symbolism as an instrument able to help the philosopher to achieve the mystical experience, by supplementing the limitations of discursive language. Furthermore, it also presents an interpretation of the geometric symbolism, present in chapter 8 of Ennead VI, 9.